2018
DOI: 10.1158/1535-7163.mct-18-0174
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Detection of ctDNA Reveals Intratumor Heterogeneity and Is Associated with Tumor Burden in Gastrointestinal Stromal Tumor

Abstract: Molecular analysis of circulating tumor DNA (ctDNA) has a large potential for clinical application by capturing tumor-specific aberrations through noninvasive sampling. In gastrointestinal stromal tumor (GIST), analysis of and mutations is important for therapeutic decisions, but the invasiveness of traditional biopsies limits the possibilities for repeated sampling. Using targeted next-generation sequencing, we have analyzed circulating cell-free DNA from 50 GIST patients. Tumor-specific mutations were detect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
49
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 45 publications
7
49
2
Order By: Relevance
“…Recently, Namlos et al . showed that detection of ctDNA in plasma of GIST patients using NGS correlated with high tumor burden but at a relevantly low ctDNA detection rate (19 of 50 patients, i.e., 38%) . Similarly, Xu et al .…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…Recently, Namlos et al . showed that detection of ctDNA in plasma of GIST patients using NGS correlated with high tumor burden but at a relevantly low ctDNA detection rate (19 of 50 patients, i.e., 38%) . Similarly, Xu et al .…”
Section: Discussionsupporting
confidence: 76%
“…22,24,26,27 It has been shown that in GIST the clonal genetic composition changes over time and secondary mutations causing treatment resistance can be detected in tissue 28,29 and plasma samples of patients with progression. 17,30 Accordingly, in Patient #5, L-PCR detected a cKIT exon 17 D820G mutation known to mediate imatinib resistance in ctDNA, 28 in addition to the preexistent cKIT exon 11 mutation, reflecting selection of a treatment-resistant disease clone contributing to subsequent progression. Targeted NGS of ctDNA offers the advantage of covering hundreds to thousands of amplicons in one assay read in an unbiased fashion.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations